Preparation of macroporous alginate-based aerogels for biomedical applications - Martins, Marta (2017)
Aerogels are a special class of ultra-light porous materials with growing interest in biomedical applications due to their open pore structure and high surface area. However, they usually lack macroporosity, while mesoporosity is typically high. In this work, carbon dioxide induced gelation followed by expansion of the dissolved CO2 was performed to produce hybrid calcium-crosslinked alginate-starch hydrogels with dual meso- and macroporosity. The hydrogels were subjected to solvent exchange and supercritical drying to obtain aerogels. Significant increase in macroporosity from 2 to 25 % was achieved by increasing expansion rate from 0.1 to 30 bar/min with retaining mesoporosity (BET surface and BJH pore volume in the range 183 â 544 m2/g and 2.0 â 6.8 cm3/g, respectively). In vitro bioactivity studies showed that the alginate-starch aerogels are bioactive, i.e. they form hydroxyapatite crystals when immersed in a simulated body fluid solution. Bioactivity is attributed to the presence of calcium in the matrix. The assessment of the biological performance showed that the aerogels do not present a cytotoxic effect and the cells are able to colonize and grow on their surface. Results presented in this work provide a good indication of the potential of the alginate-starch aerogels in biomedical applications, particularly for bone regeneration. aerogels, alginate, starch, tissue engineering, supercritical fluids, CO2 induced gelation.